Gut microbiota composition and gene expression changes induced in the Apis cerana exposed to acetamiprid and difenoconazole at environmentally realistic concentrations alone or combined - Han, Wensu; Ye, Zheyuan; Gu, Yifan; Zhong, Yihai; Gao, Jinglin; Zhao, Shan; Wang, Shijie (Frontiers in Physiology, 2023)
Apis cerana cerana is an important pollinator of agricultural crops in China. In the agricultural environment, A. c. cerana may be exposed to acetamiprid (neonicotinoid insecticide) and difenoconazole (triazole fungicide), alone or in combination, because they are commonly applied to various crops. At present, our understanding of the toxicological effects of acetamiprid and difenoconazole on honey bee gut microbiomes is limited. The primary objective of this study was to explore whether these two pesticides affect the honey bees gut microbiota and to analyse transcriptional effects of these two pesticides on honeybee head and gut. In this study, adults of A. c. cerana were exposed to acetamiprid and/or difenoconazole by contaminated syrup at field-realistic concentrations for 10 days. Results indicated that acetamiprid and/or difenoconazole chronic exposure did not affect honeybee survival and food consumption, whereas difenoconazole decreased the weight of honey bees. 16S rRNA sequencing suggested that difenoconazole and the mixture of difenoconazole and acetamiprid decreased the diversity index and shaped the composition of the gut bacteria microbiota, whereas acetamiprid did not impact the gut bacterial community. The ITS sequence data showed that neither of the two pesticides affected the fungal community structure. Meanwhile, we also observed that acetamiprid or difenoconazole significantly altered the expression of genes related to detoxifcation and immunity in the honey bee tissue. Furthermore, we found that the adverse effect of the acetamiprid and difenoconazole mixture on the honey bee health was greater than that of the single. Taken together, our study demonstrates that acetamiprid and/or difenoconazole exposure at field-realistic concentrations induced changes to the honey bee gut microbiome and gene expression.